A Study on Autoecology and Ecophysiology of Chile Piquin (Capsicum annuum Aviculare Dierb), a Wild Chilli of High Medicinal and Commercial Value in Northeast Mexico - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez; Narvaez, Ines Valencia (International Journal of Bio-resource and Stress Management, 2015)
A study has been undertaken on history, autoecology and ecophysiology of chile piquin (Capscicum annuum var. aviculare (Dierb). Studies were undertaken on morphology of the plant, root system, pollen viability, phenology, effects of water stress on growth and productivity. Morphological values were higher except dry weight in chile piquin compared to that in mouse’s eye. It possess profuse fasciculate root system occupying a greater part of soil extending to deeper depth. The percentage of pollen viability ranged from 51 to 90%, average was being 72.7%. All pigment contents were lower than that of Mouse’s eye indicatingthat chile piquin is more efficient in potential photosynthetic capacity compared to that in Mouse’s eye. It was observed clearly that the water potential of Mouse’s eye was highly fluctuating at different dates of collection, but in the case of chile piquin, it was more or less stable indicating higher level of tolerance to water stress. It indicated that the former has high capacity of extracting soil moisture even from lower soil layers. Both P, K and Fe content were higher in fruits whereas leaves contained highest content of Mg and Cu; Zn content highest in flowers. Number of leaves was higher in the treatment where application of 150 cc water was done at every two days interval, but the number decreased abruptly with increasing water stress. Growth attributes like leaves, fruits, branch numbers as well as plant height, dry weights of these had also been found to decrease with the degree of water stress.